Peningkatan Kualitas Hidup Masyarakat melalui Inovasi Ecobrick: Transformasi Sampah Plastik menjadi Nilai Ekonomis - Septiana Kurniasari; Muhammad Yunus; Mohammad Iqbal; Hilminata Saputra Sulaiman; Devi Triana Paputungan; Rila Virna (Universitas Nurul Jadid, 2024)
In 2023, there will be 141.60 tons of waste produced every day, both by households, offices, markets, commerce, public facilities and areas in Gorontalo City, and around 35% is plastic waste. The production of plastic waste in Gorontalo City is in first place. If this is allowed to continue, it will cause environmental pollution. This is because plastic waste is a type of solid waste that is difficult to decompose in a short time, which takes around 50-100 years to decompose into soil. Based on these problems, efforts need to be made to empower the community through making Ecobricks as a solution for healthy living with knowledge, faith, immunity and safety. This aims to preserve the environment, increase health independence, prevent disease and/or disasters, and increase people's income through Ecobrick products. The stages in this activity include coordination with partners, namely the Az-Zahra Mosque Ta'mirul Agency group, Pre Test, socialization regarding plastic waste, its impact on the environment and health, both in terms of science and religion, introducing the Ecobrick method as a environmentally friendly alternative plastic waste management, training in making Ecobricks, Post Test, monitoring and finishing of Ecobrick products. The results obtained from this activity include an increase in partner knowledge of around 20%, 72 Ecobrick bottles have been produced with a total of 14,309 grams of plastic waste, partner satisfaction is at 3.6 on a scale of 4, and 1 table, 4 chairs have been produced (can also be used as a table), and 1 shelf.